ADR-now application: bridging theoretical and practical approach in alternative dispute resolution process and procedures / Shahrizal Mohd Zin ... [et al.] - Mohd Zin, Shahrizal; Abdul Razak, Abdul Mu’iz; Rahmat, Nur Ezan; Fathi, Nik Hasbi (2021)
Construction Law Report, developed by the Construction Industry Development Board Malaysia (the CIDB), noted an increase in the total number of cases registered at the Specialist Construction High Court in Selangor and Wilayah Persekutuan in 2019, a rise of 14% from the previous year. This is from just one of the examples of industry in which legal disputes are piling up at the High Court, without looking at a total number of cases throughout the country and different levels of the court system. The rise of alternative dispute resolution (ADR) mechanisms is welcomed in addressing the need to resolve legal disputes between commercial and non-commercial parties. The introduction of this application is high time, noting the need for concise guidance and practical approaches to the process and procedures of ADR available in Malaysia. This application aims to provide an in-depth yet interactive platform for parties in a legal dispute to understand the nitty-gritty of ADR methods. This application will cover arbitration, adjudication, and mediation. Across industries, the tide has changed, increasing the incorporation of a dispute resolution method in commercial contracts. This is mainly evident in construction contracts, where there is almost always an agreement to arbitrate. Parties to construction contracts are also allowed to adjudicate their disputes regarding payment by resorting to the Construction Industry Payment and Adjudication Act 2012 (CIPAA 2012). The dispute resolution scene in Malaysia has become more robust with the continued acceptance of a simpler, considerably cheaper, and speedier ADR. Despite its advantages, ADR mechanisms could be arduous and complicated, depending on the complexities of each dispute. Accordingly, this ADR-Now application would greatly assist disputants who opted for any form of the ADR to be aware of each method's process and procedures. This user-friendly application employed an interactive interface that provides information with tips included to ensure a smooth process.